Functional Properties of Protein Isolates Produced by Aqueous Extraction of De‐hulled Yellow Mustard. (2nd December 2016) - Tabtabaei, Solmaz; Hijar, Benjamin; Chen, Bih King; Diosady, Levente L.
Abstract: Two types of protein isolates were prepared from de‐hulled yellow mustard flour by aqueous extraction, membrane processing and isoelectric precipitation. The precipitated and soluble protein isolates had 96.0 and 83.5% protein content on a moisture and oil free basis, respectively. Their functional properties were evaluated and compared with commercial soybean and other Brassica protein isolates. The soluble protein isolate exhibited high values for all properties. The precipitated protein isolate showed excellent oil absorption and emulsifying properties but poor solubility, water absorption and foaming properties due to its high lipid content (~25%). Storage temperature had limited effect on lipid oxidation, and hence the stability of the precipitated protein isolate at 25–45 °C. Flavor of wieners and bologna prepared with 2% of this isolate as binder was comparable to those prepared with soy protein isolate.